1996
DOI: 10.1017/s0022336000023064
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and magnetobiochronology of Tribrachiatus and Rhomboaster, two genera of Calcareous nannofossils

Abstract: The genus Tribrachiatus (all species of which are widely used stratigraphic markers) and its related genus Rhomboaster are studied in type samples and in five DSDP/ODP sites that have magnetostratigraphies and range from low through high latitudes. Rhomboaster calcitrapa, R. spineus, and R. bitrifida are shown to be junior synonyms of R. cuspis. Rhomboaster transforms into T. bramlettei by flattening of the nannolith. This makes the location of the first occurrence (FO) of T. bramlettei difficult and imprecise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…1988,1989,1990). The taxonomy of most taxa are generally well established, except for the much debated genera Rhomboaster and Tribrachiatus (Perch-Nielsen, 1985;Bybell and Self-Trail, 1997;Aubry et al, 2000;Wei and Zhong, 1996;von Salis et al, 2000;Raffi et al, 2005). Although some investigators have grouped the two under the genus Rhomboaster and recombined all species within Tribrachiatus into Rhomboaster, we prefer to distinguish both genera, only recognizing the following Rhomboaster taxa: Rhomboaster cuspis and the Rhomboaster calcitrapa group, which includes the species Rhomboaster intermedia, Rhomboaster bitrifida and Tribrachiatus spineus.…”
Section: Methodsmentioning
confidence: 99%
“…1988,1989,1990). The taxonomy of most taxa are generally well established, except for the much debated genera Rhomboaster and Tribrachiatus (Perch-Nielsen, 1985;Bybell and Self-Trail, 1997;Aubry et al, 2000;Wei and Zhong, 1996;von Salis et al, 2000;Raffi et al, 2005). Although some investigators have grouped the two under the genus Rhomboaster and recombined all species within Tribrachiatus into Rhomboaster, we prefer to distinguish both genera, only recognizing the following Rhomboaster taxa: Rhomboaster cuspis and the Rhomboaster calcitrapa group, which includes the species Rhomboaster intermedia, Rhomboaster bitrifida and Tribrachiatus spineus.…”
Section: Methodsmentioning
confidence: 99%
“…The conventional interpretation of coccolithophore systematics is that there are about 120 well-described heterococcolithophore species (Jordan and Green 1994), with, in almost all cases, interoceanic distributions within broad ecological boundaries (Jordan and Kleijne 1994;Young and Bown 1994;Jordan and Chamberlain 1997). A perception of very widely distributed, rather homogeneous species is well supported by geological evidence of synchronous, apparently sympatric evolution across the world oceans and for near synchronous (on scales of less than a few thousand years) extinction events (Chepstow-Lusty et al 1992;Wei 1993;Wei and Shilan 1996). Research over the past decade via the integration of data from various sources (morphology, life-cycles, and molecular studies) has greatly refined our knowledge of fine scale diversity in this group.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies confirmed the validity of this subdivision (e.g., Bybell and Self-Trail, 1997;Dupuis et al, 2003;Tantawy, 2006;Abu Shama et al, 2007;Faris and Salem, 2007;Al Wosabi, 2015). The subdivision of Aubry (1996) ensures the completeness of Zone NP10, but the systematic position and the range of T. digitalis were criticized (e.g., Wei and Zhong, 1996;Raffi et al, 2005).…”
Section: R F C C R R F a A F C R R F C R F R F M A 49 R F C Cmentioning
confidence: 95%
“…The evolution within the Tribrachiatus lineage is characterized by subsequent flattening and rotation, as well as the merging of the two "triplets" (e.g., Wei and Zhong, 1996). Aubry (1996) differentiated between T. digitalis marked by well-merged "triplets", T. contortus marked by well-differentiated "triplets", and T. orthostylus characterized by indistinct "triplets".…”
Section: Tribrachiatus Contortus Zone (Np10)mentioning
confidence: 99%
See 1 more Smart Citation